2019
DOI: 10.1080/2162402x.2019.1586409
|View full text |Cite
|
Sign up to set email alerts
|

Localization-associated immune phenotypes of clonally expanded tumor-infiltrating T cells and distribution of their target antigens in rectal cancer

Abstract: The degree and type of T cell infiltration influence rectal cancer prognosis regardless of classical tumor staging. We asked whether clonal expansion and tumor infiltration are restricted to selected-phenotype T cells; which clones are accessible in peripheral blood; and what the spatial distribution of their target antigens is. From five rectal cancer patients, we isolated paired tumor-infiltrating T cells (TILs) and T cells from unaffected rectum mucosa (T UM) using 13-parameter FACS single cell index sortin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 44 publications
2
25
0
Order By: Relevance
“…Personal antigen-directed therapeutic approaches have come a long way since the early days of HSCT and promise to remain a driving force for progress in hematology. The recent breathtaking technological advances have opened doors for a systematic understanding of target antigens (46,50,58), the identities and characteristics of subpopulations of TILs (160)(161)(162), and immunological aspects of disease biology (163).…”
Section: Discussionmentioning
confidence: 99%
“…Personal antigen-directed therapeutic approaches have come a long way since the early days of HSCT and promise to remain a driving force for progress in hematology. The recent breathtaking technological advances have opened doors for a systematic understanding of target antigens (46,50,58), the identities and characteristics of subpopulations of TILs (160)(161)(162), and immunological aspects of disease biology (163).…”
Section: Discussionmentioning
confidence: 99%
“…Especially the degree and type of T cell infiltration affect the prognosis of breast cancer. Some studies in many human cancers have shown that the presence of T cell infiltration is often related to good prognosis [ 12 , 13 ]. In addition, high immune infiltration was associated with increased response to neoadjuvant and adjuvant chemotherapy [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Single-cell transcriptome analysis of immune cells in tumors provides a way to comprehensively study these cells in a highly complex tumor microenvironment (TME). Recently, single-cell RNA sequencing (scRNA-seq) has been applied to tumorinfiltrating immune cells isolated from limited types of cancers, including cutaneous melanoma 7,8 , non-small cell lung cancer 9,10 , hepatocellular carcinoma 11,12 , basal cell carcinoma 13 , colorectal cancer 14,15 , and breast cancer 16 . These studies uncover significant inter-tumoral and intra-tumoral heterogeneity in tumor immune profiles, diverse immunosuppressive populations, less-defined immune cell subsets, and signal transduction networks in related cancer types.…”
mentioning
confidence: 99%